Mapping shrub biomass, Leaf Area Index and rainfall interception capacities in the Arctic tundra using L-band SAR - Chang, Qianyu (University of Guelph, 2020)
Regional-scale estimation of the shrub canopy cover in the Arctic tundra is essential to quantify their ecological and hydrological roles, especially with the recent shrub expansion driven by climate change. Synthetic-Aperture Radar (SAR) data have been shown sensitive to vegetation canopy characteristics, thereby providing an accurate and cost-effective tool to quantify shrub canopy cover and monitor its dynamics in the Arctic tundra. This study evaluated the sensitivity of L-band Advanced Land Observing Satellite 2 (ALOS-2) data to the in-situ aboveground biomass and Leaf Area Index (LAI) of dwarf birch and alder in the Trail Valley Creek watershed, Northwest Territories. Of the examined backscatter parameters, σ°HV /σ°VV showed strong sensitivity to both LAI (R2 = 0.72) and biomass (R2 = 0.63) of dwarf birch, while no strong link was observed between the alder canopy and ALOS-2 signatures. An ALOS-2 based map of birch canopy expressed by biomass and LAI was established at the watershed scale. The LAI map was fed into the Gash analytical model to estimate rainfall interception by birch canopy, an important but under-studied component of summer water balances in the Arctic tundra. Results suggest that on average across the watershed, 16.6 ± 3.2 % of incoming rainfall was intercepted by dwarf birch.